Effect of Deposit Au thin Layer Between Layers of Perovskite Solar Cell on Cell's Performance - Ahmed Ali Assi; Wasan R. Saleh; Ezzedin Mohajerani (Iraqi Journal of Physics, 2021)
The present work aims to fabricate n-i-p forward perovskite solar cell (PSC) withئ structure (FTO/ compact TiO2/ compact TiO2/ MAPbI3 Perovskite/ hole transport layer/ Au). P3HT, CuI and Spiro-OMeTAD were used as hole transport layers. A nano film of 25 nm gold layer was deposited once between the electron transport layer and the perovskite layer, then between the hole transport layer and the perovskite layer. The performance of the forward-perovskite solar cell was studied. Also, the role of each electron transport layer and the hole transport layer in the perovskite solar cell was presented. The structural, morphological and electrical properties were studied with X-ray diffractometer, field emission scanning electron microscope and current-voltage (J-V) characteristic curves, respectively. J-V curves revealed that the deposition of the Au layer between the electron transport layer (ETL) and Perovskite layer (PSK) reduced the power conversion efficiency (PCE) from 3% to 0.08% when one layer of C. TiO2 is deposited in the PSC and to 0.11% with two layers of C. TiO2. Power conversion efficiency, with CuI as the hole transport layer (HTL), showed an increase from 0.5% to 2.7% when Au layer was deposited between PSK and CuI layers. Also, Isc increased from 6.8 mA to 17.4 mA and Voc from 0.3 V to 0.5V. With depositing Au layer between P3HT and PSK layers, the results showed an increase in the efficiency from 1% to 2.6% and an increase in Isc from 10.7 mA to 30.5 mA, while Voc decreased from 0.75 V to 0.5V